The Livestock Sector Role on The Economy of Central Java - Arrizal Nurdien Fadhilah (Economics Development Analysis Journal, 2020)
The purpose of this study is to find out how big the role of the livestock sector on the economy of Central Java Province by looking at the contribution of output, demand structure, power of dispersion, sensitivity of dispersion, output multiplier, and income multiplier. The analytical method used in this study is the Input-Output analysis of Central Java Province 2013 Input-Output Table Classification of 88 Sectors. The results of the study show that the contribution of output produced by the livestock sector still low compared to the overall output produced in Central Java. The demand structure of livestock sector mostly distributed to other sectors for further production process while output of the poultry sector distributed for direct consumption. Power of dispersion analysis of the livestock sector shows the highest value among the primary sectors while the sensitivity of dispersion of livestock sector is still relatively low. Similarly, the multiplier output of livestock sector is the highest among other primary sectors, but the income multiplier of the livestock sector is still relatively low. Through input-output analysis, it can be seen the linkages between economic sectors in more detail and the impacts arising from changes that occur in one sector to other sectors. This study concludes that the livestock sector is a potential sector to be developed because it has a high value of the power of dispersion index and multiplier output so the livestocks sector expected to encourage the growth of other sectors and the economy of Central Java Province as a whole.